Intrauterine exposure to endocrine disruptors (phthalates): sources of exposure and quantification of urinary metabolites - Gómez-Mercado, Carlos Alberto; Escobar, Natalia; González, María C.; Lince, Manuela; Vásquez, María C.; Arango-Alzate, Catalina María; Segura-Cardona, Angela M.; Mejía-Sandobal, Gregory; Barraza-Villareal, Albino (Universidad y Salud, 2022)
Introduction: Phthalates are endocrine disruptors used in the manufacture of various industrial products, mainly plastics. The fetal period represents the principal window of vulnerability, and the exposure to Phthalates in this stage of life generates adverse fetal and post-natal effects. The most reliable biomarker for the assessment of Phthalates is urine. Objective: To characterize the different exposure sources of endocrine disruptors and quantify the urinary concentration of Phthalates in pregnant women. Materials and methods: A cross-sectional, observational, and descriptive study which included 400 pregnant women who received prenatal care in the Genesis and Metrosalud health institutions (Medellín-Colombia). Exposure sources were characterized and urine samples were collected from all pregnant women and the Phthalate concentration was quantified in 38 women. Results: The geometric measures of Phthalate Di(2-ethylhexyl)phthalate(DEHP), Mono-n-butyl phthalate(MnBP), Mono-2-ethyl-5-hydroxyhexyl phthalate(MEHHP) and Mono-2-ethyl-5-oxohexyl phthalate(MEOHP) were 162.72µg/L, 58.5 µg/L, 33.93µg/L and 31.63µg/L respectively. Conclusions: The majority of pregnant women that were evaluated were exposed to potential sources of endocrine disruptors throughout their life, which are present in household chemicals, tobacco, and frequent use of facial and body cosmetics. The concentrations of MnBP, MEHHP y MEOHP in urine of participants were higher than those found worldwide